Perancangan Sistem Akuntansi Penerimaan Kas Pada Pondok Pesantren Al-Muchsinun Blitar - Muhamad Shahidul Akbar; Dianita Meirini (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Al-Muchsinun Islamic Boarding School is a non-profit organization engaged in education. The financial reporting system in non-profit organizations really needs attention to assess the ability to provide services and the way managers carry out their responsibilities for the performance of Islamic boarding schools. The main source of cash receipts is obtained from payments made by students and grants. the recording system that is carried out is only in the form of simple cash records that have not been arranged so that it is necessary to make a good accounting system. This study aims to determine the existing accounting system at Pondok Al-Muchsinun as well as to design an accounting system for cash receipts that is according to the standard. The method used is descriptive qualitative. In this research, the researcher tries to describe the events and events that are the center of attention. The data used are qualitative data obtained from interviews, observations, and documentation. This research will produce recommendations for an accounting system that contains components of accounting records to finally produce a financial report. It is hoped that the preparation of the Islamic boarding school accounting system can be a reference